2017
DOI: 10.1590/0102-77863230008
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Ångström-Prescott Equation to Estimate Daily Solar Radiation on Rio Grande do Norte State, Brazil

Abstract: Knowledge of solar radiation is required for many applications. However, this atmospheric variable is not measured with an adequate space resolution. In this sense, to sites where solar radiation data are not directly measure, estimative using Ångström-Prescott equation can be used in order to provide solar radiation data, with input of sunshine duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
1
19
1
5
Order By: Relevance
“…Devido à grande quantidade e boa distribuição da precipitação na região, é evidente a influência dessas características na redução da energia solar disponível. Comparando esse valor com aqueles obtidos por Medeiros et al (2017) para três regiões semiáridas do Rio Grande do Norte, é possível observar um aumento na somatória de a e b, sendo de 0,68, 0,74 e 0,75 para Macau-RN, Caicó-RN e Apodi-RN, respectivamente. Esses resultados podem ser parcialmente explicados devido a menor precipitação acumulada anual (893, 648 e 507 mm, respectivamente), refletindo em uma atmosfera com menor presença de vapor de água e, consequentemente, menor atenuação da radiação solar total no ano.…”
Section: Methodsunclassified
See 2 more Smart Citations
“…Devido à grande quantidade e boa distribuição da precipitação na região, é evidente a influência dessas características na redução da energia solar disponível. Comparando esse valor com aqueles obtidos por Medeiros et al (2017) para três regiões semiáridas do Rio Grande do Norte, é possível observar um aumento na somatória de a e b, sendo de 0,68, 0,74 e 0,75 para Macau-RN, Caicó-RN e Apodi-RN, respectivamente. Esses resultados podem ser parcialmente explicados devido a menor precipitação acumulada anual (893, 648 e 507 mm, respectivamente), refletindo em uma atmosfera com menor presença de vapor de água e, consequentemente, menor atenuação da radiação solar total no ano.…”
Section: Methodsunclassified
“…Acta Iguazu, Cascavel, v.9, n.1, p. 123-136, 2020 Introdução A obtenção de êxito em atividades agrícolas está associada, principalmente, à exatidão das informações utilizadas para auxiliar a tomada de decisões ao longo do processo produtivo. Em produção vegetal uma das informações muito importantes é a radiação solar global, pois esse elemento climático está direta ou indiretamente relacionado aos estudos de balanço hídrico climatológico, determinação de consumo hídrico de cultivos (evapotranspiração), zoneamento agrícola e estudos hidrológicos em geral (Pereira et al, 2002).…”
Section: _____________________________________________________________unclassified
See 1 more Smart Citation
“…We have not found studies aiming to calibrate or even to validate such widely used coefficients and equations for many places in northeastern Pará. Some studies (Carvalho et al, 2011;Medeiros;Silva;Bezerra, 2017;Silva, 2014) that have been carried out for another locations in Brazil have shown that the calibrated coefficients for AP are usually different from the coefficients recommended by Allen et al (1998) and by Glover and McCulloch (1958).…”
Section: Introductionmentioning
confidence: 90%
“…Thus, it is necessary to assess the performance of empirical Rs models before application in a location where it was not previously developed. Studies have shown that local calibration of empirical constants improved Rs estimate [DE MEDEIROS et al 2017;ESTEVEZ et al 2012;ZHANG et al 2018]. For example, WU et al…”
mentioning
confidence: 99%